WEBINAR REMAJA HEBAT DENGAN MENTAL SEHAT UNTUK MENINGKATKAN PEMAHAMAN TERHADAP KESEHATAN MENTAL - Septiani Putri; Indri Cahyani; Gita Aulia; E Nurhalisa; Fitri Nur Astuti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Mental health is an important thing that must be considered like physical health. It is known that the stable condition of mental and physical health influences each other. Mental health disorders are not a complaint that can only be inherited. Life demands that have an impact on excessive stress will have an impact on worse mental health disorders. Therefor the authors are interested in implementing a webinar program that can increase understanding and knowledge and awareness of mental health for adolescents. Mental health programs can be one form of choice to increase public awareness and knowledge about mental health. The purpose of holding this webinar is to increase youth's knowledge about mental health so that it can help adolescents get the right help.